2000
DOI: 10.1111/j.1523-1755.2000.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of blood pressure control in hemodialysis patient survival

Abstract: This study confirms that hypertension is a risk factor for mortality in HD patients, and shows the importance of the length of the follow-up time to demonstrate this relationship. The low frequency of a cardiac cause in the early death group suggests that the association between hypotension and mortality in HD patients is not related to cardiovascular causes, and only reflects the association between hypotension and other severe medical conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 26 publications
5
93
0
6
Order By: Relevance
“…The changing relationship of BP with mortality over time observed in this study is in concert with a report by Mazzuchi et al (18). These investigators observed that low BP was associated with increased mortality during the early years of dialysis, whereas high BP was associated with mortality in later years.…”
Section: Discussionsupporting
confidence: 78%
“…The changing relationship of BP with mortality over time observed in this study is in concert with a report by Mazzuchi et al (18). These investigators observed that low BP was associated with increased mortality during the early years of dialysis, whereas high BP was associated with mortality in later years.…”
Section: Discussionsupporting
confidence: 78%
“…[158][159][160][161][162][163][164] As previously discussed, controversy relates to the specific relationship between the BP measurement times and technique (predialytic, postdialytic, or intradialytic BP measurements or interdialytic ambulatory BP) and morbidity and mortality. Some studies suggest an association of high BP with strokes, 165,166 cerebral atrophy, 167 cardiovascular events, 168 complex cardiac arrhythmias, 169 the development of congestive heart failure, 161 and all-cause mortality.…”
Section: Relationship Of Bp and Mortalitymentioning
confidence: 99%
“…Although an increase in the blood pressure is both a cause and a consequence of chronic kidney disease. It predisposines these patients to risk of development of left ventricular hypertrophy, congestive heart failure, stroke and other cardiovascular and neurological complications leading to high morbidity and mortality in these patients [16][17][18][19]. In the present study although all hypertensive patients were receiving antihypertensive medications yet their blood pressure were not adequately controlled which may be due to the failure to maintain optimal dry weight [20].…”
Section: Anti-hypertensive Medication and Blood Pressure Control In Hmentioning
confidence: 45%